Three-phase slurry reactors - Buwa, V. V.; Roy, S.; Ranade, V. V. (Multiphase catalytic reactors: theory, design, manufacturing, and applications, 2016)
Many of the chemical reactors employed in various sectors of the process andchemical industries, suchas petroleumrefining,downstream processing and petrochemicals, bulk and specialty chemicals, and pharmaceuticals, involve reactants and products in three phases. The ubiquitous presence of three-phase reactors comes from the fact that many of the reactants are liquids under reaction conditions, to be treated with a gas like hydrogen, and in the presence of a heterogeneous catalyst that is usually a solid. This requirement leads to two broad modes of contacting one in which the catalyst is held stationary in a "fixed" or a "packed bed" and one in which the catalyst is set free to move, along with the flowing fluid phases, during their sojourn through the reactor vessel.The choice ofwhether the catalyst should be fixed ormoving is usually dictated by the relative dominance of transport rates and intrinsic kinetics. If the reaction chemistry is intrinsically slow (when external and internalmass transfer of chemical species from the fluid phases to the porous catalyst is not rate limiting), packed bed reactor that allows very high catalyst loading is usually preferred. Packed beds, however, do not constitute the main topic of discussion in this monograph. Still, three-phase packed beds and slurry reactors are really parts of the same continuum of three-phase catalytic reactors andhave beendiscussedcomprehensively about three decades back in the classic book by P.A. Ramachandran and R.V. Chaudhari (Three Phase Catalytic Reactors. NewYork:Gordon and Breach Science Publishers; 1983). The same authors published earlier a review of three-phase slurry reactors (Chaudhari RV, Ramachandran PA. Three phase slurry reactors. AIChE J. 1980;26(2):177-199). This chapter builds on these authors' works and attempts to update the reader on developments in the field over the past few decades while retaining the essential reactionandreactorengineering aspects.The focus isonthe design, scale-up, and operation of three-phase slurry reactor systems